Knowledge Extension of Pregnant Women About Pregnancy Exercises That Can Reduce Back Pain in the Baru Ladang Bambu Village in 2021 - Sari Rahma Fitri; Suriati Lubis (Science Midwifery, 2021)
The purpose of this study was to determine whether pregnant women know that pregnancy exercise can reduce back pain (back pain. And the activities carried out are to increase the knowledge of pregnant women that pregnancy exercise can reduce back pain). Practicing pregnancy exercise to mothers and helping mothers pregnant women to take part in pregnancy gymnastics simultaneously. The types and forms of activities of this activity are as follows: Giving material to pregnant women about pregnancy exercise, demonstrating pregnancy exercise to pregnant women. The results of the research are To achieve the objectives of the above activities, activities are carried out between another delivery of material about pregnancy exercise.